Feasibility and accuracy of body-fat assessment using standardized skinfold-thickness assessment versus dual-energy X-ray absorptiometry in Paralympic athletes - van Schijndel, N.; Weijer, V.; van Loon, L. J. C.; van Dijk, J.-W. (International Journal of Sports Physiology and Performance, 2026)
Purpose: To evaluate the feasibility and accuracy of body-fat assessment using standardized skinfold-thickness assessment versus dual-energy X-ray absorptiometry (DXA) in Paralympic athletes.